Color Trails Test: A New Set of Data on Cognitive Flexibility and Processing Speed in Schizophrenia - Tyburski, Ernest; Karabanowicz, Ewa; Mak, Monika; Lebiecka, Zofia; Samochowiec, Agnieszka; Pełka-Wysiecka, Justyna; Sagan, Leszek; Samochowiec, Jerzy (Frontiers in Psychiatry, 2020)
Background: Although schizophrenia patients have been reported to manifest deficits in cognitive flexibility and lower processing speed (measured with i.a., the Color Trails Test, CTT), there still remain a few matters that require further investigation. We have therefore formulated three research aims: 1) to examine the factor structure of CTT in schizophrenia patients and healthy controls, 2) to compare different CTT performance measures in the two groups, 3) to investigate the relationship between these measures and selected psychopathological symptoms in the patient group. Methods: 67 patients with paranoid schizophrenia and 67 healthy controls, matched for gender, age, number of years of education, and overall cognitive functioning underwent assessment of cognitive flexibility and processing speed with the CTT. Results: Factor analysis of CTT variables based on the principal component method revealed a 4-factor solution in both groups. Compared with healthy controls, the patients performed poorer on CTT 1 time, CTT 2 time, 2-1 difference, prompts in CTT 2, and had higher regression factor scores for Factor 1 (reflecting the slower speed of perceptual tracking). Furthermore, significant links were found between some CTT measures and negative and disorganization symptoms. Conclusions: Schizophrenia patients exhibit problems with speed of perceptual tracking and executive processes dependent on processing speed. Our results may be useful for the development of neuropsychological diagnostic methods for schizophrenia patients. It seems that, compared to other CTT indices, CTT 1 time, CTT 2 time, and 2-1 difference are more appropriate measures of cognitive performance in schizophrenia patients.